1994
DOI: 10.1073/pnas.91.8.2935
|View full text |Cite
|
Sign up to set email alerts
|

Enterochromaffin cells of the digestive system: cellular source of guanylin, a guanylate cyclase-activating peptide.

Abstract: Guanylin, a bioactive peptide, has recently been isolated from the intet; this peptide activates intestinal guanylate cydase (i.e., guanylate cyclase C) and thus is poten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 38 publications
3
132
1
Order By: Relevance
“…Northern analysis confirms that guanylin is synthesized in the gut, especially in its distal segments (5). Guanylin is thought to modulate intestinal water/electrolyte transport in a paracrine mode (3,4,7,8). This investigation reports data on the structure of the human genesl and the circulating form of its product as well as the identification of the guanylin-containing cells in the human intestine.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Northern analysis confirms that guanylin is synthesized in the gut, especially in its distal segments (5). Guanylin is thought to modulate intestinal water/electrolyte transport in a paracrine mode (3,4,7,8). This investigation reports data on the structure of the human genesl and the circulating form of its product as well as the identification of the guanylin-containing cells in the human intestine.…”
mentioning
confidence: 69%
“…7 and 15). In addition, antisera against serotonin and chromogranin A (7,16,17) were used for the identification of endocrine cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antisera were raised in rabbits and used to localize the peptide in various tissues such as colon, liver, kidney, and stomach. Controls were carried out as routinely [6], for preabsorption tests the entire synthetic GCAP-II as well as the MAP and the linear undecapeptide were used in excess.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Northern blot and immunohistochemical analysis have revealed that guanylin occurs in the mucosa of the mammalian intestine (see reviews [4] and [5]). The peptide is probably released from entero-endocrine cells [6,7] into the intestinal lumen to activate the GC-C and consequently the chloride transport in enterocytes by means of a paracrine interaction [5]. However, several data indicate that the guanylin/GC-C system is not exclusively confined to the intestine.…”
Section: Introductionmentioning
confidence: 99%